ANALISIS PENGARUH SOSIALISASI PERPAJAKAN, KUALITAS PELAYANAN FISKUS DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Setiyoningrum, Ayu Try; Tinangon, Jantje; Wokas, Heince R.N (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
This study aims to analyze the influence of tax audit against the compliance level of corporate taxpayer to fulfilling the taxation obligations in KPP Pratama Manado(Manado Small Tax Office). The analysis method used in this research is descriptive to describe the influence of tax audit against the compliance level of corporate taxpayer to fulfilling the taxation obligations in KPP Pratama Manado. Based on the partial research results note that taxation has an influence on the socialization of individual taxpayer compliance, quality of service tax authorities have no effect on an individual taxpayer compliance and tax penalties have no effect on an individual taxpayer compliance. While based on research results simultaneously, socialization taxation, quality of service tax authorities and tax penalties as independent variables jointly affect the individual taxpayer compliance. Suggestions for KPP Pratama Manado is tax officials should be more active in conducting counseling and socialization taxes, behave professionally to serve taxpayers and improve tax penalties for taxpayers who do not comply.